Impacts of Global Warming and Elevated CO2 on Sensory Behavior in Predator-Prey Interactions: A Review and Synthesis - Draper, Alex M.; Weissburg, Marc J. (Frontiers in Ecology and Evolution, 2019)
Ecosystems are shaped by complex interactions between species and their environment. However, humans are rapidly changing the environment through increased carbon dioxide (CO2) emissions, creating global warming and elevated CO2 levels that affect ecological communities through multiple processes. Understanding community responses to climate change requires examining the consequences of changing behavioral interactions between species, such as those affecting predator and prey. Understanding the underlying sensory process that govern these interactions, and how they may be affected by climate change provides a predictive framework, but many studies examine behavioral outcomes only. This review summarizes the current knowledge of global warming and elevated CO2 impacts on predator-prey interactions with respect to the relevant aspects of sensory ecology, and we discuss the potential consequences of these effects. Our specific questions concern how climate change affects the ability of predators and prey to collect information and how this affects predator-prey interactions. We develop a framework for understanding how warming and elevated CO2 can alter behavioral interactions by examining how the processes (steps) of sensory cue (or signal) production, transmission and reception may change. This includes both direct effects on cue production and reception resulting from changes in organismal physiology, but also effects on cue transmission resulting from modulation of the physical environment via physical and biotic changes. We suggest that some modalities may be particularly prone to disruption, and that aquatic environments may suffer more serious disruptions as a result of elevated CO2 and warming that collectively affect all steps of the signaling process. Temperature by itself may primarily operate on aspects of cue generation and transmission, implying that sensory-mediated disruptions in terrestrial environments may be less severe. However, significant biases in the literature in terms of modalities (chemosensation), taxa (fish), and stressors (elevated CO2) examined currently prevents accurate generalizations. Significant issues such as multimodal compensation and altered transmission or other environmental effects remain largely unaddressed. Future studies should strive to fill these knowledge gaps in order to better understand and predict shifts in predator-prey interactions in a changing climate.